2005
DOI: 10.1111/j.1460-9568.2005.04243.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient maternal hypothyroxinemia at onset of corticogenesis alters tangential migration of medial ganglionic eminence‐derived neurons

Abstract: Correct positioning of cortical neurons during development depends on the radial migration of the projection neurons and on the coordinated tangential and radial migrations of the subcortically generated interneurons. As previously shown, a transient and moderate maternal deficiency in thyroxin during early corticogenesis alters the radial migration of projection neurons. To determine if a similar effect might also affect tangential migration of medial ganglionic eminence (MGE)-derived neurons at the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 40 publications
2
70
0
1
Order By: Relevance
“…in Zoeller and Rovet, 2004;Bernal, 2005;Bernal, 2007;Williams, 2008). The events controlled by THs comprise cellular proliferation, migration, and neuronal and glial cell differentiation (Narayanan and Narayanan, 1985;Berbel et al, 1993;Berbel et al, 1994;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Clinical and experimental studies have demonstrated that THs are essential for normal brain development.…”
Section: Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…in Zoeller and Rovet, 2004;Bernal, 2005;Bernal, 2007;Williams, 2008). The events controlled by THs comprise cellular proliferation, migration, and neuronal and glial cell differentiation (Narayanan and Narayanan, 1985;Berbel et al, 1993;Berbel et al, 1994;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Clinical and experimental studies have demonstrated that THs are essential for normal brain development.…”
Section: Nervous Systemmentioning
confidence: 99%
“…These deficits depend on specific cellular impairments. Indeed, during the prenatal period, THs influence neurogenesis, neuronal proliferation and migration in the cerebral cortex, hippocampus and medial ganglionic eminence (Narayanan and Narayanan, 1985;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Axonal outgrowth, dendritic branching and synaptogenesis, together with the initiation of glial cell differentiation and migration are also affected by TH deficiency at prenatal stages (Portfield and Hendrich, 1993;Morreale de Escobar et al, 2000;Bernal et al, 2003).…”
Section: Nervous Systemmentioning
confidence: 99%
“…When TH is missing, fundamental neurobiological processes such as neurogenesis, neuronal migration, synaptogenesis, and myelination develop atypically (7), while structures such as hippocampus (8), striatum (9), and cortex (10,11) are abnormal. Within the cortex, a late gestational/early postnatal TH insufficiency is associated with disturbed corticogenesis due to abnormal asymmetric division of neurons migrating toward the cortical surface (12).…”
mentioning
confidence: 99%
“…These substantial consequences result from the fact that even mild iodine deficiency disrupts the metabolism of thyroid hormones, which are a critical endocrine regulator of early brain development (9) . Thyroid hormones act specifically by regulating the genes that underlie major neurodevelopmental events, including neurogenesis, axon and dendrite formation, neuronal migration, synaptogenesis and myelination (10)(11)(12)(13)(14) . Thyroid hormones are also involved in the regulation of BMR and macronutrient metabolism (15) .…”
mentioning
confidence: 99%